Educational implications of food habits of Spanish-American families - Alcorn, Beatrice Warner, author; Sackett, Everett B., advisor; Williamson, Maude, advisor; Dyar, Elizabeth, committee member; Elliff, Rowan E., committee member; Burnham, Helen A., committee member; Thompson, Hazel E., committee member (Colorado State University. Libraries, 1944)
To view the abstract, please see the full text of the document.
Keywords: Diet; Nutrition; Mexican Americans